Multilocation Test of Prospective Composite Sticky Corn Varieties With High Production in Indonesia - null Edy; Andi Takdir Makkulawu; null Aminah; St Subaedah (International Journal of Agronomy)
Sticky corn is required to meet the demand for a national staple food, driven by population growth. In this context, different efforts are carried out to increase productivity by using new superior varieties with easy adaptation to specific and wider environments as well as high resistance to pests and diseases. Therefore, this research aimed to evaluate composite sticky corn variety performance in several locations in Indonesia. The method used was the adaptation testing of 4 prospective and 3 comparative varieties of composite sticky (JPI-1, JPI-2, JPI-3, and JPI-4) and (Sticky Uri, White Srikandi, and local Sticky Takalar) in 6 districts serving as research locations, respectively. Each location was designed using a randomized block design, with 4 replications to obtain 28 experimental units. Meanwhile, observation data were analyzed using analysis of variance (ANOVA). Least significant difference (LSD) test was carried out at the 5% level when there was a difference in the average value and the data analysis was conducted using the DSAASTAT program. The stability of the results was analyzed using the additive main effects and multiplicative interaction (AMMI) model through the PBSTAT program. Additionally, testing for resistance to downy mildew, rust, and leaf blight was carried out in a randomized block design with 4 replications. Proximate analysis testing was performed at the Animal Husbandry Integrated Biotechnology Laboratory, Faculty of Animal Husbandry, Hasanuddin University. The results showed that the prospective composite corn varieties JPI-1, JPI-2, JPI-3, and JPI-4 had the potential for yields significantly superior to the three comparative varieties, with 8.88, 8.54, 8.57, and 8.67 t·ha−1, respectively. In the context of the analysis, JPI-1 and JPI-4 reported stable results in all environments. Meanwhile, JPI-3 showed increasingly better results in the optimum environment. Prospective varieties JPI-1, JPI-2 JPI-3, and JPI-4 offered the criteria for resistance to Downy mildew disease Peronosclerospora maydis, Peronosclerospora philippinensis type, Bipolaris maydis type blight, and leaf rust disease type Puccinia polysora. Based on the approximate test, JPI-1, JPI-3, and JPI-4 had superior protein content of 11.64, 11.69%–11.86% than the 3 comparative varieties, respectively. The prospective variety JPI-1 had a high amylopectin content of 85.10% equivalent to local sticky parents and higher than the two comparative varieties. Additionally, JPI-2, JPI-3, and JPI-4 had higher amylopectin content than the 2 comparative varieties.